The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40614-016-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Behaviorism and Society

Abstract: A probable list of causes for the limited acceptance of behaviorism in our society is identified. This is followed by a summary review of the proposed solutions identified in other papers in this special issue of The Behavior Analyst, most of which relate to either better marketing of either the behavior analytic process or the results achieved as a consequence. One paper proposes a more broad conception of behavior analysis. This paper endorses the solutions identified in previous papers and then goes on to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In summary, researchers in the behavioral economics field of consumer choice should work more on research that: studies human behavior; can deliver rapid results; allows advanced statistical treatment; can be conducted in open natural settings; connects our science to other disciplines working on behavior; can deal with price sensitivity and the rest of the marketing mix extends individual data easily and inexpensively to large populations; can handle interrelationships of multiple variables influencing behavior; allows realistic interpretation for factors that are not easily open for experiments Therefore, we are arguing for a behavioral science of consumer and marketer behavior for its own sake, not as a symbol or sign of something else-a field where there is a bridge between behavior analysis and marketing science, and the emphasis is on direct measurements of the choice behavior in a more natural setting. Krapfl (2016) pinpoints, and we agree, that behaviorists need to specialize, that is, they need a deep understanding of one or a few business domains such as health care, financial services, or academic institutions so that it is possible to engage in serious discussions and analyses. Behavior analysis also needs to bridge over to other disciplines (Hantula 2016).…”
Section: Toward a Natural Science Of Consumer Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, researchers in the behavioral economics field of consumer choice should work more on research that: studies human behavior; can deliver rapid results; allows advanced statistical treatment; can be conducted in open natural settings; connects our science to other disciplines working on behavior; can deal with price sensitivity and the rest of the marketing mix extends individual data easily and inexpensively to large populations; can handle interrelationships of multiple variables influencing behavior; allows realistic interpretation for factors that are not easily open for experiments Therefore, we are arguing for a behavioral science of consumer and marketer behavior for its own sake, not as a symbol or sign of something else-a field where there is a bridge between behavior analysis and marketing science, and the emphasis is on direct measurements of the choice behavior in a more natural setting. Krapfl (2016) pinpoints, and we agree, that behaviorists need to specialize, that is, they need a deep understanding of one or a few business domains such as health care, financial services, or academic institutions so that it is possible to engage in serious discussions and analyses. Behavior analysis also needs to bridge over to other disciplines (Hantula 2016).…”
Section: Toward a Natural Science Of Consumer Behaviormentioning
confidence: 98%
“…According to Krapfl (2016), marketers tend to think of a marketing bifurcation that divides efforts into two foci, one pertaining to benefits and the other to attributes. Attributes describe characteristics of provider behavior or product features, whereas benefits describe what the customer gets.…”
Section: Choice-based Conjoint Analysis For Complex Situationsmentioning
confidence: 99%
“…Even though interventions based on behavior analytic principles for individuals with ASD are established as evidenced-based, their use remains contested and under-utilized in many countries (Freedman, 2016;Krapfl, 2016). One country where ABA remains particularly contested and difficult to access is France (Amoureux, 2017).…”
Section: Accuracy and Tone Of Posts In An Internet Forum On Autismmentioning
confidence: 99%
“…It is possible that, to some extent, the absence of recognition of the effectiveness of ABA for the treatment of ASD by France's higher health authorities until 2012 (Haute Autorité de Santé and Agence Nationale de l'Évaluation et de la Qualité des Établissements et Services Sociaux et Médico-Sociaux, 2012) resulted in the population's limited use of behavior analytic interventions. Researchers have also suggested that the vocabulary used by our science (e.g., "normalize", "control", "operant") and a limited understanding of the field of behavior analysis are underlying elements resulting in misconceptions regarding ethical use and effectiveness of these interventions (Freedman, 2017;Keenan, 2015;Krapfl, 2016).…”
Section: Accuracy and Tone Of Posts In An Internet Forum On Autismmentioning
confidence: 99%
“…Even though interventions based on behavior analytic principles for individuals with ASD are established as evidenced-based, their use remains contested and under-utilized in many countries (Freedman, 2016;Krapfl, 2016). One country where ABA remains particularly contested and difficult to access is France (Amoureux, 2017).…”
Section: Accuracy and Tone Of Posts In An Internet Forum On Autismmentioning
confidence: 99%